Information Literacy Debated at University of Malaya - Gill, Charlotte (Institutional Knowledge at Singapore Management University, 2009)
The International Conference on Libraries, Information and Society, ICoLIS 2008, 17-20 November, Kuala Lumpur, celebrating Information Literacy (IL) and now in its second year, is an annual event organised by the Library and Information Science Unit, Faculty of Computer Science & Information Technology, University of Malaya and the University of Malaya Library. The theme for ICoLIS 2008 was Towards an Information Literate Society.